A Prophetic Leadership Strategy for Fostering an Anti-Corruption Culture in Schools - Rifqi Fadhillah; Shafira Putri Ziyan Abidin; Muhammad Farih Ramdlani (JUMPA : Jurnal Manajemen Pendidikan, 2026)
Corruption in Indonesia's education sector remains a serious obstacle to national development, weakening institutional integrity and eroding public trust in educational governance. Existing anti-corruption initiatives in education tend to fall short because they lean almost entirely on cognitive approaches, leaving leadership ethics and organizational culture largely untouched. This study develops a conceptual framework of prophetic leadership as a strategic model for building an anti-corruption culture in schools, using a qualitative design built on a systematic literature review guided by PRISMA standards. Data drawn from reputable academic databases were analyzed through thematic analysis to construct an integrative conceptual model. The findings point to four interrelated dimensions behind prophetic leadership: siddiq (integrity) supplies the moral foundation, amanah (accountability) turns that foundation into working systems, tabligh (transparency) keeps communication open, and fathonah (wisdom) keeps the whole framework adapting rather than going stale. The study concludes that prophetic leadership offers a workable alternative to compliance-based approaches, positioning school principals as value-based leaders who can build integrity into school culture over time. This study implies that principals can embed prophetic leadership directly into school financial, personnel, communication, and curriculum management practices.